2007
DOI: 10.1097/01.ccm.0000292011.93074.82
|View full text |Cite
|
Sign up to set email alerts
|

Use of a validated delirium assessment tool improves the ability of physicians to identify delirium in medical intensive care unit patients

Abstract: Use of the ICDSC, along with education supporting its use, improves the ability of physicians to detect delirium in the medical intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 10 publications
2
62
0
1
Order By: Relevance
“…However, we feel that a single evaluator increased the consistency among the expert CAM-ICU assessments. As clinical pharmacists are now playing a leading role in delirium-related guideline development and educational efforts [6,[19][20][21], a pharmacist successfully served as the expert evaluator in this study. Second, as some evaluations were likely performed in the same patients by the same nurses, the 1011 evaluations may not have been completely independent, thereby affecting the kappa estimations.…”
Section: Discussionmentioning
confidence: 99%
“…However, we feel that a single evaluator increased the consistency among the expert CAM-ICU assessments. As clinical pharmacists are now playing a leading role in delirium-related guideline development and educational efforts [6,[19][20][21], a pharmacist successfully served as the expert evaluator in this study. Second, as some evaluations were likely performed in the same patients by the same nurses, the 1011 evaluations may not have been completely independent, thereby affecting the kappa estimations.…”
Section: Discussionmentioning
confidence: 99%
“…This only confirms the notion that delirium and acute brain dysfunction are emerging areas of knowledge where much effort is needed to unify the present definitions [21] and increase the data on pathophysiology [22][23][24], epidemiology [9,17,18], and possible interventions [7,25].…”
Section: Discussionmentioning
confidence: 81%
“…In the article written by Devlin and John W. it was shown that after physician education, agreement validated their judge for delirium identifying is more increased (22). In the article written by Gesin et al, (23) it is demonstrated that a multifaceted education program can affect the nurses' knowledge and their ability for screening of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…One of the best programs for education is educating the intensive care delirium screening checklist (ICDSC) (22,24). It seems that it is more important to educate delirium detecting to medical teams (such as doctors and nurses).…”
Section: Discussionmentioning
confidence: 99%